Awareness and use of flavor accessories for combustible tobacco products: A 2024 cross-sectional survey of high school students in Connecticut, USA - Christina N. Kyriakos; Krysten W. Bold; Meghan E. Morean; Suchitra Krishnan-Sarin; Danielle R. Davis; Grace Kong (PLoS ONE, 2026)
Significance Flavor accessories (e.g., flavor capsules), which are separate products that can be used with combustible tobacco products to alter their flavor, are on the market. These new products may bypass flavor restrictions and appeal to youth, yet no research has examined US youth awareness or use of flavor accessories. This study aimed to examine awareness and use of flavor accessories among a sample of youth in the US. Methods A school-based survey of 4,760 Connecticut high school students (mean age = 15.9, SD = 1.2) was conducted in April-May 2024. All youth reported on awareness of flavor accessories (i.e., flavor capsules, sprays/drops, cards). Youth who had ever used combustible tobacco products (i.e., cigarettes, cigars, cigarillos) or cannabis blunts, which are all products that can be used with flavor accessories (N = 868), also reported on ever use of flavor accessories. Differences in awareness by ever product user type (i.e., exclusive combustible tobacco (n = 173), exclusive blunt (n = 461), dual tobacco and blunt (n = 234)) were assessed using Bonferroni-corrected chi-square tests. Results Overall, 22.9% of youth were aware of at least one type of flavor accessory. Among ever users of combustible tobacco or blunts, awareness of at least one type of flavor accessory was 32.8%, with awareness most common for flavor capsules (19.6%), followed by sprays/drops (16.3%), and cards (9.5%). Among this group, more dual users of combustible tobacco and blunts were aware of at least one type of flavor accessory compared to exclusive users of combustible tobacco (44.1% vs 26.3%, p = 0.002) and compared to exclusive users of blunts (44.1% vs 30.8%, p = 0.005). Among ever users of combustible tobacco or blunts, ever use of any flavor accessory was 7.6%, ranging from 4.7% for flavor capsules, 3.5% for sprays/drops, and 2.7% for cards. Conclusions Nearly one-quarter of a sample of Connecticut high school youth were aware of flavor accessories, with differences in awareness by product user groups, although ever use of these products was lower. Continued monitoring of flavor accessories is critical for informing regulatory actions and interventions.